Comparison of 3 supraspinatus tendon repair techniques – a 3D computational finite element analysis. Issue 16 (9th December 2020) - Quental, C.; Reis, J.; Folgado, J.; Monteiro, J.; Sarmento, M.
Abstract: Considering that optimal contact area and pressure at the tendon-bone interface are associated with better footprint repair and outcomes, the aim of this study was to compare the performance of standard double-row, transosseous equivalent (TOE), and partial articular supraspinatus tendon avulsion (PASTA) techniques for the treatment of full-thickness tears of the supraspinatus tendon using 3D finite element models. Loading consisted, alternately, in a preloading of 10 N and 20 N of the sutures. The footprint coverage of the standard double-row, TOE, and PASTA techniques was estimated to represent 19%, 30%, and 35%, respectively, of the repair area. The average contact pressures followed an opposite trend, i.e., the largest was estimated for the standard double-row technique, whereas the lowest was estimated for the PASTA technique. Despite the present study advancing the computational modelling of rotator cuff repair, and the results being consistent with the literature, its findings must be evaluated cautiously, bearing in mind its limitations.